Single-Cell Transcriptomics Reveals Killing Mechanisms of Antitumor Cytotoxic CD4+ TCR-T Cells - Liang, Yanling; Xu, Qumiao; Liu, Songming; Li, Jie; Wang, Fei; Li, Ziyi; Liao, Lijuan; Lu, Yuting; Li, Yijian; Mu, Feng; Sun, Hai-Xi; Zhu, Linnan (Frontiers in Immunology, 2022)
T cell receptor-engineered T cells (TCR-Ts) have emerged as potent cancer immunotherapies. While most research focused on classical cytotoxic CD8+ T cells, the application of CD4+ T cells in adoptive T cell therapy has gained much interest recently. However, the cytotoxic mechanisms of CD4+ TCR-Ts have not been fully revealed. In this study, we obtained an MHC class I-restricted MART-127-35-specific TCR sequence based on the single-cell V(D)J sequencing technology, and constructed MART-127-35-specific CD4+ TCR-Ts and CD8+ TCR-Ts. The antitumor effects of CD4+ TCR-Ts were comparable to those of CD8+ TCR-Ts in vitro and in vivo. To delineate the killing mechanisms of cytotoxic CD4+ TCR-Ts, we performed single-cell RNA sequencing and found that classical granule-dependent and independent cytolytic pathways were commonly used in CD4+ and CD8+ TCR-Ts, while high expression of LTA and various costimulatory receptors were unique features for cytotoxic CD4+ TCR-Ts. Further signaling pathway analysis revealed that transcription factors Runx3 and Blimp1/Tbx21 were crucial for the development and killing function of cytotoxic CD4+ T cells. Taken together, we report the antitumor effects and multifaceted killing mechanisms of CD4+ TCR-Ts, and also indicate that MHC class I-restricted CD4+ TCR-Ts could serve as potential adoptive T cell therapies.